The Role Of The Asean Way In Vietnam's South China Sea Policy Towards China - Durmaz, Yılmaz (Institute of Social Sciences, 2017)
The aim of this work is to analyse the role of ASEAN Way of diplomacy in Vietnam's policy towards Chinese actions in the South China Sea in the period between 1995 and 2015. My main argument is that the ASEAN Way led Vietnam to show deference to China and cooperate with it in certain fields, such as joint security endeavours and the resolution process for the South China Sea dispute. The main factors that determine state behaviour are crucial for International relations theory discussions and my thesis is an attempt to discuss the ASEAN Way as an ideational factor influencing Vietnamese foreign policy. In order to examine my case, I use constructivist and realist IR schools as the theoretical framework. .

Bu çalışmanın amacı ASEAN Yolu diplomasi şeklinin, Vietnam'ın 1995-2015 arası Çin'in Güney Çin Denizi'ndeki faaliyetlerine karşılık uyguladığı politika üstündeki etkisini incelemektir. Temel argümanım ASEAN Yolu'nun Vietnam'ı Çin'e saygı gösterme ve bazı konularda işbirliği yapma konusunda yönlendirdiğidir. İşbirliği konuları arasında askeri alanlar ve Güney Çin Denizi Sorununa yönelik çözüm faaliyetleri sayılabilir. Devlet davranışlarını tetikleyen ana faktörler Uluslararası İlişkiler Teorisi tartışmaları için hayati konulardandır ve benim tezim de ASEAN Yolu'nun bir fikirsel etken olarak Vietnam dış politikasına etkisini tartışmaya çalışacak.
Vietnam'ın Çin'e Yönelik Güney Çin Denizi Politikasında Asean Yolu'nun Rolü
Thesis (M.A) -- İstanbul Technical University, Institute of Science and Technology, 2017
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: ASEAN(Association of Southeast Asian Nations); ASEAN countries; South China Sea; National interest; International relations theories; International organizations; ASEAN ülkeleri; Güney Çin Denizi; Ulusal çıkar; Uluslararası ilişkiler teorileri; Uluslararası örgütler; Uluslararası örgütler; Vietnam; Yeni gerçekçilik; Çin